Asymmetric tunneling properties in a 2D anisotropic massless linear energy system. (20th November 2019) - Yang, Cuihong; Wieser, Robert; Li, Qingfang; Zhang, Chao
Abstract: With the aid of the transfer matrix method, the carrier tunneling properties in a two-dimensional (2D) structure with an anisotropic linear energy dispersion are investigated. Several factors, the barrier structure, the incident energy, and the incident angle can be applied to modify the transmission characteristics. An impressive fact is that the anisotropic parameter and different potential directions can be used to tune the Klein tunneling. Therefore, the features of the normal incident transmission and the controllable side resonance transmission peaks can enrich the transport properties in a 2D system and are useful for the designing and utilization of electronic devices.